2015
DOI: 10.4236/ajps.2015.62040
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Legumes in a Tall Fescue Sward

Abstract: Tall fescue [Schedonorus arundinaceus (Schreb.) Dumort.] is a common grass species in the eastern half of the USA, but legumes grown with it could provide benefits. Obstacles to legume establishment in fescue pastures include disease, insect damage, and grass competition. Experiments were performed in 2010 and 2011 at Site 1 to test the efficacy of insect control, disease control, and two methods of grass suppression on seedling establishment of three legumes. The highest seedling density of red clover (Trifol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…Birdsfoot trefoil never established amid established grass competition in the current study, even with heavy autumn grazing prior to spring seeding, and was similar to the reduced establishment observed with competition by Min and Moyer (2015). White clover is easily established and widely distributed in eastern Kansas, which has abundant growing season precipitation, and white clover persistence over several years is able to substantially improve the nutritive value of cool‐season and warm‐season grass pastures (Lomas et al., 2004; Lomas & Moyer, 2020; Moyer & Lomas, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Birdsfoot trefoil never established amid established grass competition in the current study, even with heavy autumn grazing prior to spring seeding, and was similar to the reduced establishment observed with competition by Min and Moyer (2015). White clover is easily established and widely distributed in eastern Kansas, which has abundant growing season precipitation, and white clover persistence over several years is able to substantially improve the nutritive value of cool‐season and warm‐season grass pastures (Lomas et al., 2004; Lomas & Moyer, 2020; Moyer & Lomas, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…A similar reduction in biennial sweetclover also occurred in fertilized stands of predominantly warm-season grasses in western Kansas during the dry late growing season conditions of 2011 through to the very dry and droughty 2012 growing season (Harmoney et al, 2016) (Table 1). Birdsfoot trefoil never established amid established grass competition in the current study, even with heavy autumn grazing prior to spring seeding, and was similar to the reduced establishment observed with competition by Min and Moyer (2015). White clover is easily established and widely distributed in eastern Kansas, which has abundant growing season precipitation, and white clover persistence over several years is able to substantially improve the nutritive value of cool-season and warm-season grass pastures (Lomas et al, 2004;Lomas & Moyer, 2020;Moyer & Lomas, 2017).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Temperature and rainfall play significant roles in legume establishment in cover crops (Vrignon-Brenas et al, 2016). These results indicate a possible competitive effect where plants with faster growth outcompeted the legumes, which are commonly found in perennial forage systems when trying to establish legumes (Mueller and Chamblee, 1984;Butler and Muir, 2012;Min and Moyer, 2015). Additionally, studies have shown that growing combinations of legumes, including a high-growth legume (hairy vetch, Vicia villosa), contribute very little forage in a grass/brassica/legume mixture (Villalobos and Brummer, 2017).…”
Section: Mixture Compositionmentioning
confidence: 99%